IMPROVING THE TECHNOLOGIES OF DEVELOPING SPEAKING SKILLS IN A FOREIGN LANGUAGE BASED ON REAL SPEECH SITUATIONS - Turakulova Nigora Eminovna; Azamova Dilafruz Bahodirovna (Лучшие интеллектуальные исследования, 2024)
Abstract: The article provides detailed information on the improvement of technologies for the development of speaking skills in a foreign language based on real speech situations. Opinions were given on the importance of the formation of lexical skills and the level of importance of teaching speech in the development of speech skills. The role and tasks of English grammar and methodology in the development of oral speech skills were explained. The influence of psychophysiological mechanisms of oral speech on the development of speech was revealed in detail. Opinions on the use of innovative methods in the use of oral speech in English were discussed. It was discussed in detail about the plans being carried out in our country for the development of oral speech skills.